Elderly and Children Are Not The Only Victims of Foreign Body Airway Obstruction in Italy (A National Media-Based Survey) - G Landoni; T. Scquizzato; A. G. Yavorovskiy; A. Zangrillo; S. Silvetti (Общая реаниматология, 2021)
Choking is a relevant public health problem. Data in medical literature are scarce and fatal events are dramatically under-reported.The aim of this manuscript is to give a real estimation of this problem and to raise awareness about this topic.Materials and methods. All deaths caused by choking reported by Italian Mass Media over a two years period were collected. Suspected sudden infant death syndrome was an exclusion criteria.Results. 76 deaths due to foreign body airway obstruction were identified, 51% during 2018 and 49% in 2019, without identifiable time clusters. Choking affected every age, including pre-scholar children (25%), children 6 to 18 years old (3%), adults (38%), and elderly patients (34%). Witnessed cases were 61 (80%) but in almost half 26 cases (42%) the fatal event occurred before or without first aid maneuvers being performed.Conclusion. On the Italian territory, during a 2 years period, three cases per month of fatal choking due to foreign-body airway obstruction occurred, many of them in adult patients (38%). Italian people seem not to be educated to provide first aid in these settings.